ESCHATOLOGICAL HOPE AND APOCALYPTIC MOOD IN POETRY - Xursanov Dilshod Baxtiyorovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the themes of eschatological hope and apocalyptic mood in poetry. It analyzes how poets use images of destruction, spiritual crisis, and existential anxiety while also expressing hope for renewal and transformation. Drawing on the works of T. S. Eliot, Robert Frost, and William Wordsworth, the study shows that apocalyptic poetry reflects both fear of collapse and belief in spiritual rebirth. The article concludes that poetry transforms human anxiety into philosophical and artistic reflection.